Effect of Laser Heating on Partial Decomposition of Bi12SiO20 (BSO) Single Crystal: Raman Study - Romcevic, Nebojsa; Hadzic, Branka; Prekajski Đorđević, Marija; Mihailovic, Peda; Curcic, Milica; Trajic, Jelena; Mitric, Jelena; Romcevic, Maja (Journal of Spectroscopy, 2023)
The effect of laser (532 nm line of Verdi G) heating during the Raman measurements, on partial decomposition of Bi12SiO20 single crystal, was addressed in this study. The degree of decomposition directly depends on the power density and duration of the laser treatment, which are registered by the phonon Raman spectra. After laser treatment, AFM measurements register additional small spherical islands on the surface. Analysis performed on irradiated and unirradiated samples showed significant changes in transmission spectra, X-ray diffraction (XRD) pattern, Verdet constant, magneto-optical property, and absorption coefficient. The material obtained after laser irradiation can be described as specific nanocomposite consisting of bismuth oxide and silicon oxide-based nano-objects (dimensions below 15 nm in diameter), which are arranged in a matrix of Bi12SiO20.